The Difference in Fermentation Duration of Plant-Based Feed Using EM4 on the Feed Quality - Manganang, Yessi A. P.; Ulaan, Magdalin; Mose, Numisye I. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
EM-4 probiotic solution is used in a fermentation process to lower the crude fiber in lemna cake and raise the protein content of the raw materials. The research aims to determine the difference in fermentation duration of plant-based feed using EM-4 solution on the improvement of quality and nutritional value of Nile tilapia feed. The object of the research is artificial feed with 30% protein composed of various vegetable ingredients which is then fermented according to the research design. The study was consisting of 4 treatments: A: 1-day fermentation, B: 3-day fermentation, C: 5-day fermentation, D: 7-day fermentation. Data collection involved chemical and physical testing of the feed. The results of this research showed that the longer the fermentation, the protein content becomes higher while the carbohydrate and crude fiber content decreases. Therefore, the physical tests of the feed included buoyancy, water stability, and feed hardness shows no difference in each treatment. Seven days fermentation shows the best values on nutritional values. The combination of EM-4 with artificial feed made from vegetable ingredients can be recommended as fish feed because it fulfills protein nutritional needs to increase fish growth and development.